2005
DOI: 10.1002/app.22091
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pH‐response swelling behavior of poly(2‐ethyl‐2‐oxazoline)/chitosan interpenetrating polymer network hydrogels

Abstract: ABSTRACT:Interpenetrating polymer network (IPN) hydrogels composed of poly(2-ethyl-2-oxazoline) (PEtOz) and chitosan (CS) were prepared with radical polymerization and were characterized for their swelling properties. Sample OC11 (hydrogel weight ratio PEtOz/CS ϭ 1/1) swelled more than samples OC21 (PEtOz/CS ϭ 2/1) and OC31 (PEtOz/CS ϭ3/1), exhibiting a swelling ratio of about 2000 wt % in deionized water; the swelling ratios of the other samples were about 1000 and 700 wt %. The swelling behavior of the IPN h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…These hydrogels exhibited reversible swelling-deswelling behavior upon step-wise change of temperature from 20 to 70 °C. Similarly, Kim reported reversible temperature-induced swelling-deswelling cycles for interpenetrating network hydrogels of cross-linked PEtOx macromonomer with poly(vinyl alcohol) (PVA) [41] or chitosan [42]. Albertson et al reported the synthesis and swelling behavior of ternary microgel particles consisting of PNIPAM, PHEMA, and PMeOx or PEtOx [43].…”
Section: Thermoresponsive Poly(2-oxazoline)-based Hydrogelsmentioning
confidence: 98%
“…These hydrogels exhibited reversible swelling-deswelling behavior upon step-wise change of temperature from 20 to 70 °C. Similarly, Kim reported reversible temperature-induced swelling-deswelling cycles for interpenetrating network hydrogels of cross-linked PEtOx macromonomer with poly(vinyl alcohol) (PVA) [41] or chitosan [42]. Albertson et al reported the synthesis and swelling behavior of ternary microgel particles consisting of PNIPAM, PHEMA, and PMeOx or PEtOx [43].…”
Section: Thermoresponsive Poly(2-oxazoline)-based Hydrogelsmentioning
confidence: 98%
“…The hydrogel in a swollen state maintains a soft and rubbery state comparable to living tissues and displays excellent biocompatibility (Ju et al, 2002). Among various hydrogels, chitosan-based hydrogels have been the focus of study by many investigators (Kim et al, 2006;Ahn et al, 2002) due to its relatively high biocompatibility and ability to be cross-linked, thereby rendering a threedimensional network structure to it. The network structure prevents a dosage form from dissolving easily in the medium, and the extended drug release from the swollen gel structure can thus be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Among various polymers, hydrogels have been widely used in the development of various controlled release matrix tablets (Kim et al, 2006;Noble et al, 1999). The hydrogel in a swollen state maintains a soft and rubbery state comparable to living tissues and displays excellent biocompatibility (Ju et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[37] Interessanterweise ermöglichte die Kontrolle der Triblockcopolymer-Zusammensetzung die Absenkung des [77] oder Chitosan. [78] In einer neueren Untersuchung berichteten David et al über die Synthese und das Quellungsverhalten ternärer Mikrogelpartikel, die aus NIPAM, HEMA und PMeOx-oder PEtOx-Makromonomeren bestehen. [79] Beim…”
Section: Thermoresponsive Hydrogeleunclassified